Virtual Education Trials and Evaluation Process in Architecture - Hilmi Ekin OKTAY; Hacer MUTLU DANACI; Melisa UNVAN; Kemal Reha KAVAS; İbrahim BAKIR (Anı Publishing, 2021)
The word 'virtual,' which the entire world has become familiar with during the pandemic in 2020, was a phrase that is primarily applicable for higher education in various departments. However, for design students, the online learning medium is a new concept, and the question of how the virtual teaching environment affects the design capability of students is pertinent regarding architectural and design education. This study explores how architectural students' perception of their education medium affects their success in organizational behavior. In this context, an in-depth online interview that aims to understand the perception of architectural students regarding their education medium was conducted to analyze the effects of the learning medium on their educational success. The findings obtained in this study may improve architectural education concerning the virtual teaching experience.